KATAGORI DAN EKSPRESI LINGUISTIK WADAH BERBAHAN DASAR BAMBU PADA MASYARAKAT JAWA: KAJIAN ETNOLINGUSITIK - Akhmad Dzukaul Fuad; Shendy Andrie Wijaya; Gandung Wirawan (JURNAL SOSIAL HUMANIORA (JSH), 2018)
This study aims to describe the form of lexicon in the Java language (bJ) which has the meaning of bamboo-based container. The description is based on the formation of lexicon not necessarily formed and spoken without considering the external aspects of the language (metabahasa) that exist in the community of speakers. Meta The language that became the starting point and the basis of categorization makes this research not only involves linguistic analysis but a combination of linguistics and anthropology and commonly called etnolinguistik. The lexicon categorization of bamboo-based containers in Javanese is adapted to the form, the domain of use and the meta aspects of the language reflected in each lexicon. From the analysis results obtained three domains of use and overall leksikon nouns.